2005
DOI: 10.1038/sj.bjc.6602682
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of TIP (paclitaxel, ifosfamide and cisplatin) given as second-line (post-BEP) salvage chemotherapy for patients with metastatic germ cell cancer: a medical research council trial

Abstract: This phase II trial describes the use of TIP chemotherapy (paclitaxel, ifosfamide and cisplatin) as salvage for patients with metastatic germ cell cancer (GCC) who have failed initial BEP (bleomycin, etoposide and cisplatin) chemotherapy. Patients with first relapse following BEP for metastatic GCC, confirmed by biopsy or sequentially rising markers, received four courses of TIP (paclitaxel 175 mg m À2 day 1, followed on days 1 -5 by ifosfamide 1 g m À2 intravenously (i.v.) and cisplatin 20 mg 2 i.v.) at 3-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 33 publications
(62 reference statements)
2
41
0
1
Order By: Relevance
“…Motzer et al [16] reported their findings in 46 patients with recurrent GCTs treated with TIP, achieving a very high CR rate of 77 %. Mead et al [17] subsequently reported similar but somewhat inferior results with less-intensive TIP in a second-line salvage setting, showing a response rate of 38 %. Despite being encouraging response rates in a salvage setting, TIP failed to lead to a marked improvement in long-term disease remission compared with conventional salvage chemotherapies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Motzer et al [16] reported their findings in 46 patients with recurrent GCTs treated with TIP, achieving a very high CR rate of 77 %. Mead et al [17] subsequently reported similar but somewhat inferior results with less-intensive TIP in a second-line salvage setting, showing a response rate of 38 %. Despite being encouraging response rates in a salvage setting, TIP failed to lead to a marked improvement in long-term disease remission compared with conventional salvage chemotherapies.…”
Section: Discussionmentioning
confidence: 70%
“…1 Overall survival in 20 patients with advanced germ cell tumors who were judged to be refractory or relapsed after BEP (bleomycin, etoposide, and cisplatin) and TIP (cisplatin, ifosfamide and paclitaxel) therapies, and subsequently received irinotecan and nedaplatin powerful activity against such intractable GCTs [16,17]. Motzer et al [16] reported their findings in 46 patients with recurrent GCTs treated with TIP, achieving a very high CR rate of 77 %.…”
Section: Discussionmentioning
confidence: 96%
“…27 The chance of cure depends on the extent of disease at relapse and initial sensitivity of the disease. A recent multivariate analysis identified five prognostic groups with a chance of cure, varying from less than 10% to over 70%.…”
Section: How Are Patients Who Do Not Respond To Initial Chemotherapy mentioning
confidence: 99%
“…Impressive results have been reported using either conventional-dose chemotherapy (CDCT) or high-dose chemotherapy with stem cell rescue (HDCT). [1][2][3][4] However, these reports from single institutions are confounded by patient selection. A single randomized trial comparing CDCT to a HDCT strategy has been completed and reported as negative, but has also been subject to criticism and refuted to some degree by a large single institutional report influential in suggesting benefit of HDCT at first salvage.…”
Section: Introductionmentioning
confidence: 99%